2019
DOI: 10.1038/s41467-019-12264-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in striatal dopamine release is governed by release-independent depression and the dopamine transporter

Abstract: Mesostriatal dopaminergic neurons possess extensively branched axonal arbours. Whether action potentials are converted to dopamine output in the striatum will be influenced dynamically and critically by axonal properties and mechanisms that are poorly understood. Here, we address the roles for mechanisms governing release probability and axonal activity in determining short‐term plasticity of dopamine release, using fast‐scan cyclic voltammetry in the ex vivo mouse striatum. We show that brief short‐term facil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 72 publications
5
53
0
Order By: Relevance
“…The DA system is therefore also sensitive to a local presynaptic modulation from other neurotransmitters (like acetylcholine or endocannabinoids) ( Xu et al., 2018 ). DAT exerts a main presynaptic master control on DA release as recently demonstrated ( Condon et al., 2019 ; Walters et al., 2020 ). DA release is in fact directly modulated at the presynaptic terminals by a Rho-dependent internalization of DAT.…”
Section: Section 1: Dopamine Receptorsmentioning
confidence: 79%
“…The DA system is therefore also sensitive to a local presynaptic modulation from other neurotransmitters (like acetylcholine or endocannabinoids) ( Xu et al., 2018 ). DAT exerts a main presynaptic master control on DA release as recently demonstrated ( Condon et al., 2019 ; Walters et al., 2020 ). DA release is in fact directly modulated at the presynaptic terminals by a Rho-dependent internalization of DAT.…”
Section: Section 1: Dopamine Receptorsmentioning
confidence: 79%
“…GABA B receptor activation slightly promotes the ratio of evoked DA release by high-frequency trains over single pulse release (see Figure 1 ) [ 36 , 37 , 39 ], consistent with a reduction in the initial release probability of DA, and consequently, a slight relief of short-term depression. We have recently revealed that mechanisms that determine axonal excitability, particularly potassium-dependent processes, strongly gate short-term plasticity of DA release [ 82 ]. Tonic activation of GABA B receptors on DA axons might plausibly provide a persistent axonal permeability to potassium through activation of Kir3-type potassium channels, and we therefore hypothesise that tonic GABA B activity might facilitate changes to short-term plasticity of DA release in response to conditions that change the driving force on potassium entry.…”
Section: Gaba B Receptor Modulation Of Da Axonamentioning
confidence: 99%
“…Mounting evidence has demonstrated that DAT represents a critical regulator of terminal release and plasticity via regulation of the temporal dynamics of dopamine in the extracellular space (Condon, Platt, & Zhang, 2019). DAT is a low capacity, high affinity transporter expressed on dopamine neurons and can be found on dopamine cell bodies, their dendrites, and their axonal projections (Ciliax et al., 1995; Freed et al., 1995).…”
Section: Homosynaptic Regulation At the Terminalmentioning
confidence: 99%